Children With Cystic Fibrosis Are Infected With Multiple Subpopulations of Mycobacterium abscessus With Different Antimicrobial Resistance Profiles. (26th January 2019) - Shaw, Liam P; Doyle, Ronan M; Kavaliunaite, Ema; Spencer, Helen; Balloux, Francois; Dixon, Garth; Harris, Kathryn A
Abstract: Background: Children with cystic fibrosis (CF) can develop life-threatening infections of Mycobacterium abscessus . These present a significant clinical challenge, particularly when the strains involved are resistant to antibiotics. Recent evidence of within-patient subclones of M. abscessus in adults with CF suggests the possibility that within-patient diversity may be relevant for the treatment of pediatric CF patients. Methods: We performed whole-genome sequencing (WGS) on 32 isolates of M. abscessus that were taken from multiple body sites of 2 patients with CF who were undergoing treatment at Great Ormond Street Hospital, United Kingdom, in 2015. Results: We found evidence of extensive diversity within patients over time. A clustering analysis of single nucleotide variants revealed that each patient harbored multiple subpopulations, which were differentially abundant between sputum, lung samples, chest wounds, and pleural fluid. The sputum isolates did not reflect the overall within-patient diversity and did not allow for the detection of subclones with mutations previously associated with macrolide resistance ( rrl 2058/2059). Some variants were present at intermediate frequencies before the lung transplants. The time of the transplants coincided with extensive variation, suggesting that this event is particularly disruptive for the microbial community, but the transplants did not clear the M. abscessus infections and both patients died as a result of these infections. Conclusions: Isolates of M. abscessus from sputum do not always reflect the entire diversity present within the patient, which can include subclones with differing antimicrobial resistance profiles. An awareness of this phenotypic variability, with the sampling of multiple body sites in conjunction with WGS, may be necessary to ensure the best treatment for this vulnerable patient group. Abstract : Children with cystic fibrosis undergoing lung transplants harbor multiple subpopulations of Mycobacterium abscessus. Subpopulations can have different antimicrobial resistance genotypes. Sputum isolates do not reflect the genetic diversity within a patient.